Analysis Of Tiktok Video Content In The Incident Of UNP Student Eviction By Residents: A Case Study Of Perceptions And Impacts - Desiana (Feedback International Journal of Communication, 2024)
This study aims to analyze video content on TikTok related to incidents of KKN UNP students being expelled by residents and examine their perceptions and impacts in a social context. In this case study, an in-depth review of the video content made by UNP KKN students and residents involved in the incident was carried out. The research method used is video content analysis and a case study approach. Through an analysis of the messages and narration in the video content on TikTok regarding the expulsion incident, it is described and interpreted. The results of this study reveal that the messages in the video content play an important role in shaping the narrative and influencing the people's perspective on the event. This research also found the factors that influence the perception and impact of video content on TikTok as well as understanding of the role of social media in shaping public opinion and its effect on social dynamics, such as people's perception of the video content and its impact through public attitudes.